(untitled) (Sustainability in Debate, 2023)
This essay reflects on the oil-dependent model and its relationship with vulnerability in the health of small-scale fishing communities from the Social Determination of Health perspective. Three analysis axes were structured as follows: characterising the industry’s dependence on fossil fuels and the consequences for the populations of the affected territories; the Brazilian oil disaster crime in 2019; and f inally, considering Breilh’s conception (2013), characterising the social determination of health in the vulnerable territories affected by these disasters. The notion of health dissociated from social, cultural, economic, spiritual, and political constructions represents an insufficient model for analysing the healthdisease process, identifying a fragmented being and disregarding the overlapping of "inorganic" layers that suppresses and reorganises existence.